2018
DOI: 10.1002/elsc.201700130
|View full text |Cite
|
Sign up to set email alerts
|

Covalent immobilization of acetylcholinesterase on a novel polyacrylic acid‐based nanofiber membrane

Abstract: In this study, polyacrylic acid‐based nanofiber (NF) membrane was prepared via electrospinning method. Acetylcholinesterase (AChE) from Electrophorus electricus was covalently immobilized onto polyacrylic acid‐based NF membrane by demonstrating efficient enzyme immobilization, and immobilization capacity of polymer membranes was found to be 0.4 mg/g. The novel NF membrane was synthesized via thermally activated surface reconstruction, and activation with carbonyldiimidazole upon electrospinning. The morphology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 41 publications
(55 reference statements)
1
14
0
Order By: Relevance
“…immobilized AChE on polyacrylic acid-based nanofiber and they stated that the optimum pH values for free AChE and immobilized AChE was 7.5 and 8.0, respectively. [38] Moradzadegan et al found AChE immobilized PVA/bovine serum albumin nanofibers and they didn't observe alteration the optimum pH values after the immobilization process. [36] The enzyme stability is affected by pH changes.…”
Section: Temperature Propertiesmentioning
confidence: 99%
See 3 more Smart Citations
“…immobilized AChE on polyacrylic acid-based nanofiber and they stated that the optimum pH values for free AChE and immobilized AChE was 7.5 and 8.0, respectively. [38] Moradzadegan et al found AChE immobilized PVA/bovine serum albumin nanofibers and they didn't observe alteration the optimum pH values after the immobilization process. [36] The enzyme stability is affected by pH changes.…”
Section: Temperature Propertiesmentioning
confidence: 99%
“…Çakıroğlu et al immobilized AChE onto polyacrylic acid/based nanofiber membrane and the optimal temperature for AChE was 30°C while it was 35°C for immobilized AChE. [38] Ebadi et al prepared AChE immobilized polyacrylic acid/multi-walled carbon nanotube nanofiber the optimum temperature values of free AChE and immbolizied AChE was 40 and 45°C, respectively. [39] Both free and immobilized AChEs were incubated for 1 h at different temperatures (30-60°C) to determine the effect of temperature on free AChE and immobilized AChE stability.…”
Section: Temperature Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Polymeric materials with antimicrobial activity are used in many fields, particularly in medical devices technology, drug delivery systems, health care products and hygienic applications 1‐9 . One particular approach for therapeutic applications is the use of polymeric carriers or polymer active substance conjugate systems.…”
Section: Introductionmentioning
confidence: 99%